High-flame-retardant coating diaphragm for lithium battery and preparation method of high-flame-retardant coating diaphragm
By applying a flame retardant paste composed of modified hollow glass microspheres and melamine cyanurate on the lithium-ion battery separator, the problem of the lithium-ion battery separator is easily shrinkable at high temperatures, improving flame retardancy and ionic conductivity, and enhancing the safety and performance of the battery.
Patent Information
- Application Number
- CN202510680107.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-08-05
AI Technical Summary
The existing lithium-ion battery separators are prone to shrinking and deforming in high temperature environments, resulting in short circuits in the battery, posing safety hazards, and conventional flame retardants will affect the ionic conductivity and performance of the battery.
The flame retardant slurry consisting of modified hollow glass microspheres, nano-scale hexagonal sheet melamine cyanurate, magnesium hydroxide and boehmite were coated on the base film through a microgravure roller coating process, and a uniform coating was formed by combining polyimide and acrylic copolymer to enhance flame retardancy and ionic conductivity.
It improves the flame retardancy and ionic conductivity of the lithium battery separator, reduces the risk of thermal runaway at high temperatures, and enhances the safety and performance stability of the battery.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a highly flame-retardant coated diaphragm for a lithium battery and a preparation method thereof. Background Art
[0002] Traditional lithium-ion batteries are widely used in the modern energy sector, but safety issues remain a key factor hindering their further development. As one of the key components of batteries, lithium-ion battery separators play a vital role in their performance and safety.
[0003] Currently, traditional lithium-ion battery separators are primarily made of polyolefins (such as PE and PP). While these materials offer advantages such as low cost and excellent mechanical properties, they also have significant drawbacks. Their low melting point makes them susceptible to shrinkage and deformation at high temperatures. Once the separator shrinks, direct contact between the positive and negative electrodes can easily lead to a short circuit, thermal runaway, and even fires, explosions, and other serious safety hazards. This poses a significant risk to the large-scale application of lithium-ion batteries.
[0004] To improve the heat resistance and flame retardancy of polyolefin separators, the industry has tried a variety of conventional solutions. One of these is to prepare ceramic-coated separators, which involves coating the surface of polyolefin separators with ceramic materials such as Al2O3, SiO2, and boehmite. These ceramic coatings can, to a certain extent, improve the separator's heat resistance and reduce shrinkage at high temperatures. However, this solution also has significant drawbacks. Ceramic particles are prone to powdering in high-temperature environments, and the ceramic material itself cannot effectively protect the polyolefin separator at high temperatures. The separator may still fail due to high temperatures, thereby affecting battery safety.
[0005] Another common approach is to use flame-retardant additives in separators, essentially adding a flame retardant to the coating material to achieve a flame-retardant effect. However, when using small molecule flame retardants, excessive addition can clog the pores of the coated separator, hindering ion passage. This not only reduces the battery's ionic conductivity but also negatively impacts the battery's cycle rate and capacity, leading to reduced battery performance and failure to meet the high energy density and long cycle life requirements of practical applications.
[0006] Hollow glass microspheres are considered an ideal flame-retardant filler due to their low density, high melting point, low thermal conductivity, and chemical inertness. Their application in lithium-ion battery separators is expected to improve the flame retardancy of the separator while reducing the weight of the battery and increasing its energy density. However, the current application of hollow glass microspheres in separators still faces many technical bottlenecks. For example, the bonding between the hollow glass microspheres and the separator coating is weak, and they easily fall off during the battery charging and discharging process, affecting the stability and flame retardant effect of the separator. At the same time, the flame retardant synergistic mechanism of hollow glass microspheres in the separator is still unclear, making it difficult to fully exert their flame retardant properties, limiting their large-scale application in lithium-ion battery separators.
[0007] In summary, there is an urgent need to develop a coated separator for lithium batteries that can effectively improve the flame retardancy of lithium battery separators and ensure that the separators have good ionic conductivity. Summary of the Invention
[0008] The purpose of the present invention is to provide a highly flame-retardant coated diaphragm for lithium batteries and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.
[0009] The technical solution for achieving the purpose of the present invention is: In a first aspect, the present invention provides a highly flame-retardant coated diaphragm for a lithium battery, comprising a base film and a flame-retardant slurry layer coated on the surface of the base film; the raw material components of the flame-retardant slurry include, by mass fraction, 0.2% to 0.7% dispersant, 0.1% to 0.5% wetting agent, 1% to 5% magnesium hydroxide, 5% to 10% composite binder, 18 to 22% boehmite, 5% to 10% modified hollow glass microspheres, and the rest is ultrapure water.
[0010] Furthermore, the flame retardant filler includes modified hollow glass microspheres and nano-scale hexagonal flake melamine cyanurate; the modified hollow glass microspheres are obtained by modifying hollow glass microspheres with a silane coupling agent.
[0011] Furthermore, the composite adhesive is obtained by compounding acrylic copolymer and polyimide; Furthermore, the acrylic copolymer is obtained by reacting acrylic acid, butyl acrylate, and diethyl allyl phosphate and then grafting 1,3-dibromopropane.
[0012] Furthermore, the polyimide is obtained by a mixed reaction of β-nicotinamide adenine dinucleotide lithium salt and biphenyltetracarboxylic dianhydride.
[0013] In a second aspect, the present invention provides a method for preparing a highly flame-retardant coated separator for a lithium battery as described in the first aspect, the preparation steps being as follows: (1) Premixing of the composite adhesive: 10 parts by mass of acrylic acid copolymer and 43-45 parts by mass of dimethyl sulfoxide were mixed and stirred for 55-65 minutes, followed by adding 1-3 parts by mass of polyimide, and refluxed at 90-100°C for 23-25 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, and the solvent was removed by distillation under reduced pressure to obtain a composite adhesive; The premixing mechanism is as follows: ; (2) Weigh and prepare the ingredients according to the mass fraction of each raw material component; (3) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (2) are added to ultrapure water and stirred to disperse uniformly, followed by adding a composite binder and a flame retardant filler, and stirring is continued for 28 to 32 minutes. After that, a wetting agent is added and stirred for 8 to 12 minutes to obtain a flame retardant slurry; (4) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating; (5) Pre-solidify for 3 to 8 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 40 to 60°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
[0014] Furthermore, the preparation steps of the polyimide are as follows: under nitrogen protection, 5.18~5.35 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.18~1.2 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring at room temperature is continued for 23~25 hours. Then, the mixture is baked in a conventional oven at 60°C for 2 hours, 80°C for 2 hours, 100°C for 2 hours, 120°C for 2 hours, and 150°C for 2 hours, and then baked in a vacuum oven at 250°C for 2 hours, 300°C for 2 hours, and 350°C for 2 hours to obtain polyimide.
[0015] Furthermore, the preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.1-0.3 parts by mass of octyl acrylate, 0.8-1.2 parts by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 44-46° C. under nitrogen protection, 4.25-4.35 parts by mass of ammonium persulfate as an initiator is added, and the mixture is reacted at a constant temperature for 7.5-8.5 hours, the mixture is repeatedly washed with ethanol and dried 3-4 times, and then 44 parts by mass of dimethyl sulfoxide is added, 1,3-dibromopropane is added at a rate of 1 second / drop / , the mixture is reacted at 155-165° C. for 4 hours, and then the mixture is naturally cooled to room temperature under a nitrogen environment, and 1,3-dibromopropane and dimethyl sulfoxide are removed by distillation under reduced pressure to obtain an acrylic copolymer; The preparation mechanism is as follows: .
[0016] By adopting the above technical solution, the present invention has the following beneficial effects: (1) The highly flame-retardant coated diaphragm for lithium batteries of the present invention comprises a base film and a flame-retardant slurry layer coated on the surface of the base film; wherein the raw material components of the flame-retardant slurry include, by mass fraction, 0.2% to 0.7% of a dispersant, 0.1% to 0.5% of a wetting agent, 1% to 5% of magnesium hydroxide, 5% to 10% of a composite binder, 18% to 22% of boehmite, 5% to 10% of a flame-retardant filler, and the remainder is ultrapure water. By introducing magnesium hydroxide, a composite binder, boehmite, and a flame-retardant filler into the flame-retardant slurry, the highly flame-retardant coated diaphragm for lithium batteries has good flame retardancy and ionic conductivity.
[0017] (2) The flame retardant filler of the present invention includes modified hollow glass microspheres and nano-scale hexagonal flake melamine cyanurate, which have good flame retardant effect. Among them, the hollow glass microspheres are composed of inorganic materials, and the interior is a closed microsphere filled with carbon dioxide gas, and has the advantages of light weight, low thermal conductivity, non-toxicity, non-flammability, good chemical stability, and high dispersion. At high temperatures, the microspheres melt to form a dense glass barrier, isolating oxygen from contact with the electrolyte. At the same time, as the spheres rupture, the gas inside the microspheres expands due to heat and absorbs heat, reducing the risk of thermal runaway. At the same time, the hollow glass microspheres optimize the pore structure, reduce the coating density, provide a heat insulation layer, and the composite coating design synergistically improves the performance of the coated diaphragm.
[0018] (3) The present invention modifies the hollow glass microspheres by using a silane coupling agent to enhance the dispersibility of the hollow glass microspheres in the slurry and the bonding force in the coating.
[0019] (4) The present invention introduces magnesium hydroxide, which decomposes at high temperatures to produce water vapor, which can effectively suppress the thermal runaway of the battery and enhance the flame retardancy of the coated diaphragm for highly flame-retardant lithium batteries.
[0020] (5) The boehmite introduced in the present invention can play a supporting role.
[0021] (6) The polyimide of the present invention is prepared from β-nicotinamide adenine dinucleotide lithium salt and biphenyltetracarboxylic dianhydride. β-nicotinamide adenine dinucleotide lithium salt is composed of phosphoric acid, pentose and base. It is a three-source bio-based flame retardant. Phosphoric acid serves as an acid source, pentose serves as a carbon source, and base serves as a gas source. The "three sources" effectively match during the combustion process to form a non-combustible carbon foam layer with a closed space structure and release non-combustible gas, effectively cutting off the heat exchange between the polymer and the outside world and diluting the concentration of the surrounding air, ultimately causing the polymer to self-extinguish. It can effectively combine the condensed phase flame retardant and the gas phase flame retardant to work together to synergistically retard the flame retardant, further improving the flame retardancy of the coated diaphragm for high flame retardant lithium batteries; at the same time, the introduction of β-nicotinamide adenine dinucleotide lithium salt can provide free Li⁺ through dissociation, directly enhancing the ionic conductivity of the diaphragm.
[0022] (7) The acrylic copolymer of the present invention is obtained by reacting acrylic acid, butyl acrylate, and allyl diethyl phosphate and then grafting 1,3-dibromopropane, which can effectively increase the flame retardancy of the coated separator for high flame retardant lithium batteries.
[0023] (8) The adhesive of the present invention is obtained by compounding polyimide and acrylic copolymer, wherein the bromopropane on the acrylic copolymer reacts and grafts with the imidazole ring on the polyimide to form an imidazole salt ionic liquid, which forms a uniform ion transport network in the slurry, further enhancing the ionic conductivity of the reinforced diaphragm. DETAILED DESCRIPTION
[0024] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0026] The following examples are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.
[0027] The raw materials of Examples and Comparative Examples are as follows: Modified hollow glass microspheres: 50 g of hollow glass microspheres with a D50 of 15 μm were placed in a vacuum oven at 80°C and dried for 12 h, and then cooled to room temperature; 140 ml of ethanol and 10 ml of ultrapure water were added to a 250 mL three-necked round-bottom flask, stirred evenly, and acetic acid was added to adjust the pH of the aqueous solution to 5.5. 0.44 g of vinyltrimethoxysilane was added and hydrolyzed for 1 h. Subsequently, the aforementioned hollow glass microspheres were added, the temperature was raised to 60°C and refluxed at a constant temperature for 5 h. After the temperature was lowered to room temperature, the mixture was filtered, washed three times with ethanol, and dried to obtain modified hollow glass microspheres.
[0028] Glyceryl monostearate is used as dispersant; The wetting agent used was TEGO® Wet 270; The base film is a polypropylene (PP) porous base film with a thickness of 5 microns.
[0029] (Example 1) A method for preparing a highly flame-retardant coated diaphragm for lithium batteries, the preparation steps are as follows: (1) Premixing of the composite adhesive: 10 parts by mass of acrylic acid copolymer and 43 parts by mass of dimethyl sulfoxide were mixed and stirred for 55 minutes, followed by the addition of 1 part by mass of polyimide. The mixture was refluxed at 90°C for 23 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and the solvent was removed by distillation under reduced pressure to obtain a composite adhesive. (2) Weigh and prepare the ingredients according to the mass fraction of each raw material component: 0.45% dispersant, 0.1% wetting agent, 3% magnesium hydroxide, 6% composite binder, 20% boehmite, 5% modified hollow glass microspheres, and the rest is ultrapure water; (3) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (2) are added to ultrapure water and stirred and dispersed uniformly, followed by adding a composite binder and modified hollow glass microspheres, and stirring is continued for 28 minutes. After that, a wetting agent is added and stirred for 8 minutes to obtain a flame retardant slurry; (4) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the surface of the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating with a thickness of 5 μm on both sides; (5) Pre-solidify for 3 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 40°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
[0030] The polyimide is prepared as follows: under nitrogen protection, 5.18 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.18 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring is continued at room temperature for 23 hours. Then, the mixture is baked in a conventional oven at 60° C. for 2 hours, 80° C. for 2 hours, 100° C. for 2 hours, 120° C. for 2 hours, and 150° C. for 2 hours, and then baked in a vacuum oven at 250° C. for 2 hours, 300° C. for 2 hours, and 350° C. for 2 hours to obtain the polyimide.
[0031] The preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.1 parts by mass of octyl acrylate, 0.8 parts by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 44° C. under nitrogen protection, 4.25 parts by mass of initiator ammonium persulfate is added, and the mixture is reacted at a constant temperature for 7.5 hours, the mixture is repeatedly washed with ethanol and dried three times, and then 44 parts by mass of dimethyl sulfoxide is added, and 1,3-dibromopropane is added at a rate of 1 second / drop / time, the mixture is reacted at 155° C. for 4 hours, and the mixture is naturally cooled to room temperature under a nitrogen environment. The 1,3-dibromopropane and dimethyl sulfoxide are removed by distillation under reduced pressure to obtain the acrylic copolymer.
[0032] (Example 2) A method for preparing a highly flame-retardant coated diaphragm for lithium batteries, the preparation steps are as follows: (1) Premixing of the composite adhesive: 10 parts by mass of acrylic acid copolymer and 44 parts by mass of dimethyl sulfoxide were mixed and stirred for 60 minutes, followed by the addition of 2 parts by mass of polyimide, and the mixture was refluxed at 95°C for 24 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, and the solvent was removed by distillation under reduced pressure to obtain a composite adhesive; (2) The ingredients were weighed according to the mass fraction of each raw material component: 0.55% dispersant, 0.1% wetting agent, 3% magnesium hydroxide, 8% composite binder, 20% boehmite, 8% modified hollow glass microspheres, and the rest was ultrapure water; (3) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (2) are added to ultrapure water and stirred and dispersed uniformly, followed by adding a composite binder and modified hollow glass microspheres, and stirring is continued for 30 minutes. After that, a wetting agent is added and stirred for 10 minutes to obtain a flame retardant slurry; (4) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the surface of the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating with a thickness of 5 μm on both sides; (5) Pre-solidify for 6 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 50°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
[0033] The polyimide is prepared as follows: under nitrogen protection, 50.28 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.19 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring is continued at room temperature for 24 hours. Then, the mixture is baked in a conventional oven at 60° C. for 2 hours, 80° C. for 2 hours, 100° C. for 2 hours, 120° C. for 2 hours, and 150° C. for 2 hours, and then baked in a vacuum oven at 250° C. for 2 hours, 300° C. for 2 hours, and 350° C. for 2 hours to obtain the polyimide.
[0034] The preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.2 parts by mass of octyl acrylate, 1 part by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 45° C. under nitrogen protection, 4.3 parts by mass of initiator ammonium persulfate is added, and the mixture is reacted at a constant temperature for 8 hours, the mixture is repeatedly washed with ethanol and dried three times, and then 44 parts by mass of dimethyl sulfoxide is added, and 1,3-dibromopropane is added at a rate of 1 second / drop / time, the mixture is reacted at 160° C. for 4 hours, and the mixture is naturally cooled to room temperature under a nitrogen environment, and 1,3-dibromopropane and dimethyl sulfoxide are removed by distillation under reduced pressure to obtain the acrylic copolymer.
[0035] (Example 3) A method for preparing a highly flame-retardant coated diaphragm for lithium batteries, the preparation steps are as follows: (1) Premixing of the composite adhesive: 10 parts by mass of acrylic acid copolymer and 45 parts by mass of dimethyl sulfoxide were mixed and stirred for 65 minutes, followed by the addition of 3 parts by mass of polyimide. The mixture was refluxed at 100°C for 25 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and the solvent was removed by distillation under reduced pressure to obtain a composite adhesive. (2) Weigh and prepare the ingredients according to the mass fraction of each raw material component: 0.55% dispersant, 0.1% wetting agent, 3% magnesium hydroxide, 10% composite binder, 20% boehmite, 10% modified hollow glass microspheres, and the rest is ultrapure water; (3) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (2) are added to ultrapure water and stirred and dispersed uniformly, followed by adding a composite binder and modified hollow glass microspheres, and stirring is continued for 32 minutes. After that, a wetting agent is added and stirred for 12 minutes to obtain a flame retardant slurry; (4) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the surface of the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating with a thickness of 5 μm on both sides; (5) Pre-solidify for 8 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 60°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
[0036] The polyimide is prepared as follows: under nitrogen protection, 5.35 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.2 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring is continued at room temperature for 25 hours. Then, the mixture is baked in a conventional oven at 60° C. for 2 hours, 80° C. for 2 hours, 100° C. for 2 hours, 120° C. for 2 hours, and 150° C. for 2 hours, and then baked in a vacuum oven at 250° C. for 2 hours, 300° C. for 2 hours, and 350° C. for 2 hours to obtain the polyimide.
[0037] The preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.3 parts by mass of octyl acrylate, 1.2 parts by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 46° C. under nitrogen protection, 4.35 parts by mass of ammonium persulfate as an initiator is added, and the mixture is reacted at a constant temperature for 8.5 hours, the mixture is repeatedly washed with ethanol and dried four times, and then 44 parts by mass of dimethyl sulfoxide is added, and 1,3-dibromopropane is added at a rate of 1 second / drop / time, the mixture is reacted at 165° C. for 4 hours, and the mixture is naturally cooled to room temperature under a nitrogen environment. The 1,3-dibromopropane and dimethyl sulfoxide are removed by distillation under reduced pressure to obtain the acrylic copolymer.
[0038] (Comparative Example 1) The difference between Comparative Example 1 and Example 2 is that the raw material components of the coated diaphragm for highly flame-retardant lithium batteries include: 0.55% dispersant, 0.1% wetting agent, 8% composite binder, 28% boehmite, and the rest is ultrapure water. The remaining steps and components are the same as those in Example 2.
[0039] (Comparative Example 2) The difference between Comparative Example 2 and Example 2 is that the composite adhesive is prepared by copolymerizing an alkali-soluble acrylic resin with a molecular weight between 1700 and 16000 and an acid value greater than 90 with polyimide, and the rest is ultrapure water. The remaining steps and components are the same as those in Example 2.
[0040] (Comparative Example 3) The difference between Comparative Example 3 and Example 2 is that the composite adhesive only uses acrylic copolymer, and the remaining steps and components are the same as those of Example 2.
[0041] (Comparative Example 4) A method for preparing a highly flame-retardant coated diaphragm for lithium batteries, the preparation steps are as follows: (1) The raw materials were weighed and prepared according to the mass fraction of each component: 0.55% dispersant, 0.1% wetting agent, 3% magnesium hydroxide, 8% composite binder, 20% boehmite, 8% modified hollow glass microspheres, and the rest was ultrapure water; (2) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (1) are added to ultrapure water and stirred and dispersed uniformly, followed by adding a composite binder and modified hollow glass microspheres, and stirring is continued for 30 minutes. After that, a wetting agent is added and stirred for 10 minutes to obtain a flame retardant slurry; the mass ratio of acrylic copolymer to polyimide in the composite binder is 10:2; (3) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the surface of the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating with a thickness of 5 μm on both sides; (4) Pre-solidify for 6 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 50°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
[0042] The polyimide is prepared as follows: under nitrogen protection, 50.28 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.19 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring is continued at room temperature for 24 hours. Then, the mixture is baked in a conventional oven at 60° C. for 2 hours, 80° C. for 2 hours, 100° C. for 2 hours, 120° C. for 2 hours, and 150° C. for 2 hours, and then baked in a vacuum oven at 250° C. for 2 hours, 300° C. for 2 hours, and 350° C. for 2 hours to obtain the polyimide.
[0043] The preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.2 parts by mass of octyl acrylate, 1 part by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 45° C. under nitrogen protection, 4.3 parts by mass of initiator ammonium persulfate is added, and the mixture is reacted at a constant temperature for 8 hours, the mixture is repeatedly washed with ethanol and dried three times, and then 44 parts by mass of dimethyl sulfoxide is added, and 1,3-dibromopropane is added at a rate of 1 second / drop / time, the mixture is reacted at 160° C. for 4 hours, and the mixture is naturally cooled to room temperature under a nitrogen environment, and 1,3-dibromopropane and dimethyl sulfoxide are removed by distillation under reduced pressure to obtain the acrylic copolymer.
[0044] (Effect example) Ionic conductivity: The high flame retardant lithium battery prepared in the examples and comparative examples was soaked in electrolyte with a coated separator and sandwiched between stainless steel sheets. The SS / Separator / SS battery was assembled and the separator impedance was measured. The measurement frequency range was 1×10 6 Hz-10Hz, AC amplitude is 10 mV, the intercept of the curve on the X-axis in the Nyquist plot obtained by electrochemical impedance spectroscopy is the impedance of the diaphragm after being immersed in the electrolyte, and the ionic conductivity of the diaphragm = diaphragm thickness / (area of the stainless steel sheet*diaphragm impedance).
[0045] Flame retardancy: The highly flame-retardant lithium batteries prepared in the examples and comparative examples were ignited and the burning time was observed and recorded.
[0046] Table 1 below shows the performance test results of the highly flame-retardant coated separators for lithium batteries of Examples 1 to 3 and Comparative Examples 1 to 4:
[0047] As shown in Table 1 above, the highly flame-retardant coated separators for lithium batteries of Examples 1 to 3 and Comparative Examples 1 to 4 have good flame retardancy and high ionic conductivity.
[0048] The difference between Comparative Example 1 and Example 2 is that modified hollow glass microspheres are not added to the raw material components of the highly flame-retardant coated diaphragm for lithium batteries, and the obtained highly flame-retardant coated diaphragm for lithium batteries has low ion conductivity and poor flame retardancy.
[0049] The difference between Comparative Example 2 and Example 2 is that the composite binder is obtained by compounding polyimide and commercially available polyacrylic acid resin, and the resulting highly flame-retardant coated separator for lithium batteries has low ion conductivity and poor flame retardancy.
[0050] The difference between Comparative Example 3 and Example 2 is that the composite binder uses only acrylic copolymer, and the resulting highly flame-retardant coated separator for lithium batteries has low ion conductivity and poor flame retardancy.
[0051] The difference between Comparative Example 4 and Example 2 is that the polyimide and acrylic copolymer in the composite binder are not pre-mixed, and the ionic conductivity of the prepared highly flame-retardant coated separator for lithium batteries is low.
[0052] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A highly flame-retardant coated separator for lithium batteries, characterized in that: It includes a base film and a flame retardant slurry layer coated on the surface of the base film; the raw material components of the flame retardant slurry include, by mass fraction, 0.2% to 0.7% dispersant, 0.1% to 0.5% wetting agent, 1% to 5% magnesium hydroxide, 5% to 10% composite binder, 18% to 22% boehmite, 5% to 10% flame retardant filler, and the rest is ultrapure water.
2. The highly flame-retardant coated separator for lithium batteries according to claim 1, characterized in that: The flame retardant filler comprises modified hollow glass microspheres and nano-scale hexagonal flake melamine cyanurate; the modified hollow glass microspheres are obtained by modifying hollow glass microspheres with a silane coupling agent.
3. The highly flame-retardant coated separator for lithium batteries according to claim 1, characterized in that: The composite adhesive is obtained by compounding acrylic copolymer and polyimide.
4. The highly flame-retardant coated separator for lithium batteries according to claim 3, characterized in that: The acrylic copolymer is obtained by reacting acrylic acid, butyl acrylate and diethyl allyl phosphate and then grafting 1,3-dibromopropane.
5. The highly flame-retardant coated separator for lithium batteries according to claim 3, characterized in that: The polyimide is obtained by a mixed reaction of β-nicotinamide adenine dinucleotide lithium salt and biphenyltetracarboxylic dianhydride.
6. A method for preparing a highly flame-retardant coated separator for a lithium battery according to any one of claims 1 to 5, characterized in that: The preparation steps are as follows: (1) Premixing of the composite adhesive: 10 parts by mass of acrylic acid copolymer and 43-45 parts by mass of dimethyl sulfoxide were mixed and stirred for 55-65 minutes, followed by adding 1-3 parts by mass of polyimide, and refluxed at 90-100°C for 23-25 hours. After the reaction was completed, the mixture was naturally cooled to room temperature, and the solvent was removed by distillation under reduced pressure to obtain a composite adhesive; (2) Weigh and prepare the ingredients according to the mass fraction of each raw material component; (3) The weighed dispersant, boehmite, and magnesium hydroxide prepared in step (2) are added to ultrapure water and stirred to disperse uniformly, followed by adding a composite binder and a flame retardant filler, and stirring is continued for 28 to 32 minutes. After that, a wetting agent is added and stirred for 8 to 12 minutes to obtain a flame retardant slurry; (4) Using a micro-gravure roller coating process, the flame retardant slurry is evenly rolled onto the base film through a coating machine, and the excess slurry is scraped off with a smoothing roller to form a uniform coating; (5) Pre-solidify for 3 to 8 seconds in an environment with a humidity of ≥90%, wash with water to remove the residual solvent, and then dry and solidify at 40 to 60°C to obtain a highly flame-retardant coated diaphragm for lithium batteries.
7. The method for preparing a highly flame-retardant coated separator for a lithium battery according to claim 6, wherein: The polyimide is prepared as follows: under nitrogen protection, 5.18 to 5.35 parts by mass of β-nicotinamide adenine dinucleotide lithium salt and 44 parts by mass of dimethyl sulfoxide are mixed, stirred at room temperature until completely dissolved, and then 1.18 to 1.2 parts by mass of biphenyltetracarboxylic dianhydride are added, and stirring is continued at room temperature for 23 to 25 hours. Then, the mixture is baked in a conventional oven at 60° C. for 2 hours, 80° C. for 2 hours, 100° C. for 2 hours, 120° C. for 2 hours, and 150° C. for 2 hours, and then baked in a vacuum oven at 250° C. for 2 hours, 300° C. for 2 hours, and 350° C. for 2 hours to obtain the polyimide.
8. The method for preparing a highly flame-retardant coated separator for a lithium battery according to claim 6, wherein: The preparation steps of the acrylic copolymer are as follows: 10 parts by mass of acrylic acid, 0.1-0.3 parts by mass of octyl acrylate, 0.8-1.2 parts by mass of allyl diethyl phosphate, 4 parts by mass of an emulsifier, and 40 parts by mass of pure water are mixed and stirred until fully emulsified and dissolved, the pH is adjusted to 7, the mixture is heated to 44-46° C. under nitrogen protection, 4.25-4.35 parts by mass of ammonium persulfate as an initiator is added, and the mixture is reacted at a constant temperature for 7.5-8.5 hours, the mixture is repeatedly washed with ethanol and dried 3-4 times, and then 44 parts by mass of dimethyl sulfoxide is added, and 1,3-dibromopropane is added at a rate of 1 second / drop / time, the mixture is reacted at 155-165° C. for 4 hours, and then the mixture is naturally cooled to room temperature under a nitrogen environment, and 1,3-dibromopropane and dimethyl sulfoxide are removed by reduced pressure distillation to obtain the acrylic copolymer.
Citation Information
Patent Citations
Ceramic separator and lithium ion battery
CN107195837A
Preparation method of fly ash floating bead-coated non-woven fabric diaphragm
CN110165125A
Battery diaphragm and preparation method thereof
CN116544605A
Battery fireproof partition plate, preparation method of battery fireproof partition plate, battery module and new energy automobile
CN116565441A
Method for manufacturing organic-inorganic porous separator for secondary battery, and organic-inorganic porous separator manufactured therefrom
WO2014104687A1
Cited By
Boehmite coated diaphragm and preparation process thereof
CN121086554A